المکتبات العامة فی ریف محافظتی أسیوط والوادی الجدید: دراسة میدانیة - د. مها محمود ناجى ق (المجلة الدولية لعلوم المكتبات والمعلومات)
This paper studies all public libraries established by the CulturalDevelopment Fund with the name (Child and Youth Library). Out of which; fourare in Assiut Governorate countryside, three are in the New Valley Governorate.The study examines the current state of these libraries, and their role as a meansfor the overall development in the rural community. This is done throughobserving the most important activities and services provided by the libraries toits' patrons and assessing the extent of benefit from them. Moreover, identifyingthe obstacles facing libraries' users and proposing solutions, in order to enhancethe performance of these libraries. Also, pinpointing the right framework for theestablishment of public libraries in this rural and remote areas. Finally, identifyingpolicies related to the services provided by these libraries for the residents ofthese areas.